Identifikasi jenis batuan mengunakan metode geolistrik tahanan jenis konfigurasi wenner (Identification of rock types using the geoelectric resistivity method of the Wenner configuration ) - Sendi Mutia; - Akmam; Harman Amir (Department of Physics – Universitas Negeri Padang UNP, 2018)
The government of Padang has done the planning the development region construction . The region construction planning will be done in Kelurahan Balai Gadang. The construction is focused to the society residence. Hence, it is needed the knowledge about the various rocks under the surface for the design construction. The purpose of this research is to know the resistivity and kinds of rock arrangement under the surface. The research is a basic descriptive research. Measurement were made using the Geolistrik resistivity method of the wenner configuration.The wenner configuration has good vertical resolution so it is good to use for knowing rock types. The interpretation of the data was used Software Res2dinv to get resistivity and depth of rocks in 2D model cross section below the earth surface.The result of this research shows the kinds of resistivity in kelurahan balai gadang Kecamatan KotoTangah is line1 1,79 Ωm - 6020 Ωm ,line2 3,03 Ωm – 14.810 Ωm, line3 1,8 Ωm – 6747 Ωm, and line4 8,85 Ωm – 2490 Ωm. There are 5 kinds of arrangementrocks in Kelurahan Balai Gadang suck as Alluvium, Sandstone, Clay, Limestone and Andisite.